Liminality and Emotional Labor among war widows in Israel. (December 2019) - Ben-Asher, Smadar; Bokek-Cohen, Ya'arit
This article focuses on Israeli army widows from the religious-Zionist sector and the Bedouin sector. We show how these women are compelled by their cultural context to either suffer liminal identity or to invest in exhausting Emotional Labor and fake their authentic selves. The surrounding society expects much more Emotional Labor of religious-Zionist widows than of their Bedouin counterparts; in contrast, the societal status of Bedouin widows remains liminal, as compared to that of the religious-Zionist widows, who anchor their identity relatively quickly. The findings highlight the need to sensitively assist army widows with the Liminality and Emotional Labor that hinder their personal and familial rehabilitation. The findings are analyzed critically within the framework of the Zižekian approach, which investigates the elusive power of ideology over the agency of the individual's self in society.